Secondary metabolite analysis in the broad host range plant pathogenic fungus Sclerotinia sclerotiorum: Secondary metabolite analysis in the broad host range plant pathogenic fungus Sclerotinia sclerotiorum - NAVIN C GUPTA; SHAWETA ARORA; MAHESH RAO; PANKAJ SHARMA (Journal of Oilseeds Research, 2023)
Secondarymetabolites are known to play a vital role in host-pathogen interaction wherein little is knownabout the secondary metabolites secreted by S. sclerotiorum in axenic culture. In this study, we predicted the genomic repertoire of the metabolites in an Indian isolate ‘ESR-01’ of the S. sclerotiorum and analysed the secondary metabolites secreted by pathogenically diverse Indian isolates of the S. sclerotiorum in axenic culture through untargeted high-resolution UPLC-QTOF-ESI/MS. We also investigated the phylogenetic correlation among these isolates based on metabolic profiling with the pathogenicity and ITS-based diversity analysis of the pathogen published earlier.